Coastal Karst Landforms - Mylroie, John E.; Lace, Michael J. (Coastal Research Library, 2013)
Carbonate rock coasts are found world-wide, from continental shorelines of the Adriatic Sea of Europe to the Yucatan Peninsula of North America, and on tropical islands from Rodrigues Island in the Indian Ocean, to the Mariana Islands in the Pacific Ocean, to the Bahama Islands in the Atlantic Ocean.  Such coasts are well known for their unusual and distinctive karst landforms. Karst processes, particularly those associated with coastal landforms, are proving to be surprisingly unique and complex. This volume presents a comprehensive overview of the processes associated with coastal karst development comparing examples from a broad geographical and geomorphological range of island and continental shoreline/paleoshoreline settings, including a review of pseudokarst processes that can compete with and overprint dynamic coastal karst landscapes. As effective management of hydrologic resources grows more complex, coastal caves and karst represent fundamental components in associated coastal aquifers, which in the rock record can also form significant petroleum reservoirs. Audience  By providing a clearer understanding of the geological, biological, archaeological and cultural value of coastal caves and karst resources, this volume offers a critical tool to coastal researchers and geoscientists in related fields and to coastal land managers as it illustrates the diversity of coastal karst landforms, the unique processes which formed them, the diversity of resources they harbor and their relationship to coastal zone preservation strategies and the development of sustainable management approaches.